An α-D-galactan and a β-D-glucan from the mushroom Amanita muscaria: Structural characterization and antitumor activity against melanoma. (15th November 2021) - Zavadinack, Matheus; de Lima Bellan, Daniel; da Rocha Bertage, Jessica Loren; da Silva Milhorini, Shayane; da Silva Trindade, Edvaldo; Simas, Fernanda Fogagnoli; Sassaki, Guilherme Lanzi; Cordeiro, Lucimara M.C.; Iacomini, Marcello
Abstract: Polysaccharides α-D-galactan (GAL-Am) and β-D-glucan (GLC-Am) were obtained from Amanita muscaria fruiting bodies. They were purified using different methodologies, such as Fehling precipitation (for both fractions), freeze-thawing process and ultrafiltration (for GLC-Am). Results showed that the GAL-Am has (1 → 6)-linked Gal p main chain branched at O -2 by terminal Gal p units and has not been previously reported. Besides, GLC-Am has (1 → 3)-linked Glc p in the main chain, substituted at O -6 by (1 → 6)-linked β-Glc p units. Both are water-soluble, with 9.0 × 10 3  g/moL and 1.3 × 10 5  g/moL, respectively. GAL-Am and GLC-Am presented a selective proliferation reduction against B16-F10 melanoma cell line, not affecting non tumoral BALB/3T3 fibroblast cell line. Furthermore, both fractions reduced clonogenic capacity of melanoma cell line over an extended period of time. These results were obtained without modulations in B16-F10 cell adhesion, reinforcing the biological activities towards cell proliferation impairment and eliciting these polysaccharides as promising compounds to further exploration of their antimelanoma properties. Highlights: An α-D-galactan and a β-D-glucan were purified from Amanita muscaria mushroom and chemically characterized. The galactan has (1 → 6)-linked Gal p main chain branched at O-2 by terminal Gal p units and has not been previously reported. The glucan has (1 → 3)-linked Glc p in the main chain, substituted at O -6 by (1 → 6)-linked β-Glc p units. Both presented a selective cell viability and proliferation reduction against B16-F10, not affecting BALB/3T3 cell line. Both fractions reduced B16-F10 colony area and formation capacity over an extended period of time.